Answered

At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Get quick and reliable solutions to your questions from a community of experienced professionals on our platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

solve for c: 5c-4-2c+1=8c+2

Sagot :

cpk
Original equation: 5c-4-2c+1=8c+2
The first thing you want to do is combine like terms:
3c-3=8c+2
Then. get the variable on its own side by subtracting the 3c from the left and subtracting the 2 from the right:
-5=5c
Divide both sides by 5 to get c by itself:
-1=c
daos
collect like terms so it will become
5c-2c-8c=4plus2minus1
therefore it will become -5c divided by -5 = 5divided by -5
 ans c=-1